Solve for m 9(m+2)=-6(m+7)

Math
9(m+2)=-6(m+7)
Simplify 9(m+2).
Tap for more steps…
Apply the distributive property.
9m+9⋅2=-6(m+7)
Multiply 9 by 2.
9m+18=-6(m+7)
9m+18=-6(m+7)
Simplify -6(m+7).
Tap for more steps…
Apply the distributive property.
9m+18=-6m-6⋅7
Multiply -6 by 7.
9m+18=-6m-42
9m+18=-6m-42
Move all terms containing m to the left side of the equation.
Tap for more steps…
Add 6m to both sides of the equation.
9m+18+6m=-42
Add 9m and 6m.
15m+18=-42
15m+18=-42
Move all terms not containing m to the right side of the equation.
Tap for more steps…
Subtract 18 from both sides of the equation.
15m=-42-18
Subtract 18 from -42.
15m=-60
15m=-60
Divide each term by 15 and simplify.
Tap for more steps…
Divide each term in 15m=-60 by 15.
15m15=-6015
Cancel the common factor of 15.
Tap for more steps…
Cancel the common factor.
15m15=-6015
Divide m by 1.
m=-6015
m=-6015
Divide -60 by 15.
m=-4
m=-4
Solve for m 9(m+2)=-6(m+7)

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top